Risk of birth defects and perinatal outcomes in HIV-infected women exposed to integrase strand inhibitors during pregnancy. (2nd February 2021) - Sibiude, Jeanne; Le Chenadec, Jérôme; Mandelbrot, Laurent; Dollfus, Catherine; Matheron, Sophie; Lelong, Nathalie; Avettand-Fenoel, Véronique; Brossard, Maud; Frange, Pierre; Reliquet, Véronique; Warszawski, Josiane; Tubiana, Roland
Abstract : Objectives: Following an alert on neural tube defects and dolutegravir, we sought to evaluate if the exposure integrase strand transfer inhibitors (INSTIs) at conception was associated with birth defects or other adverse pregnancy outcomes. Methods: In the prospective national French Perinatal Cohort (EPF), we studied birth defects and other perinatal outcomes by matching each pregnant woman exposed to INSTIs with a pregnant woman exposed to darunavir/ritonavir receiving the same backbone of nucleoside reverse transcriptase inhibitors and matched for other characteristics such as age, geographic origin, centre and year of delivery. Results: Among 808 women exposed to INSTIs during pregnancy (raltegravir = 703, dolutegravir = 57 and elvitegravir = 48), we reported a slightly higher rate of birth defects in infants exposed at conception to raltegravir (6.7%) vs. infants exposed to raltegravir later in pregnancy: 2.9% if initiated during pregnancy as first-line, and 2.5% as second-line treatment,   P  =0.04. When compared with matched controls, raltegravir exposure at conception was not significantly associated with birth defects: 6.4 vs. 2.3%, P  = 0.08. There was no cluster of birth defect type and no neural tube defects were observed. Other perinatal outcomes, such as preterm birth and stillbirths, did not differ significantly between raltegravir-exposed women and matched counterparts. No difference in any outcome was observed for elvitegravir/cobicistat or dolutegravir. Conclusion: We found a nonsignificant trend for an association between exposure to raltegravir at conception and birth defects, which needs to be evaluated by larger prospective surveillance data, as these drugs are increasingly prescribed in women living with HIV.